Bacterial Cellulose Production in The Overripe Guava Juice by Acetobacter xylinum as A Solution to Reduce Organic Waste - Annisa Nur Lathifah; Isa Nuryana (Research Center for Chemistry - LIPI, 2021)
The exploration for a new cost-effective carbon source with shorter fermentation process for high yield BC production is still needed. In this study, bacterial cellulose (BC) was synthesized by Acetobacter xylinum using overripe guava juice as a carbon source. The results showed that A. xylinum was able to grow on the overripe guava juice with different concentration and produced BC after two days incubation. In the later on, the BC is called as nata de guava. The overripe guava juice which containing reducing sugar content 23 g /L (substrate 100%) at pH 4 produced the thickest BC (1.267 cm). This study showed due to the high reducing sugar and protein contents in the overripe guava, without the addition of carbon and nitrogen from external sources, BC could be formed. Considering the huge disposal overripe guava fruit waste in Java, the present study provides an alternative methodology to synthesize BC. Besides, most importantly, this study provides a new insight to manage organic waste specifically from overripe guava fruit rather than the waste being thrown away and becoming organic waste generation. Keywords: bacterial cellulose, Acetobacter xylinum, overripe guava, organic waste